Incompletely condensed POSS-based spin-on-glass networks for impeccable ultra low-k integration - Lee, Albert S.; Choi, Seung-Sock; Oh, Sung Yeoun; Lee, He Seung; Kim, Bomin; Hwang, Seung Sang; Baek, Kyung-Youl (ROYAL SOC CHEMISTRY, 2015)
Poly(methyl) silsesquioxane-based spin-on-glass resins incorporating both a cyclic precursor, 1,3,5,7-tetramethyl 1,3,5,7-tetrahydroxyl cyclosiloxane, and incompletely condensed methyl-substituted POSS were synthesized and their thermal, mechanical, and electrical properties were investigated as a function of the POSS loading content. By introducing incompletely condensed methyl-substituted POSS compounds at the molecular level as sol-gel precursors, exceptional thermal stability (4700 degrees C), good mechanical properties (elastic modulus >4.0 GPa), and an ultra-low dielectric constant (k = 1.8) were obtained. In addition to providing a new route towards fully poly(methyl) silsesquioxane-based spin-on-glass resins with the above properties, the realization of the application of integration circuits was evaluated to show that the ultra low-k, mechanically robust spin-on-glass materials were able to withstand harsh wet chemical and dry etching, as well as chemical mechanical planarization (CMP) processing.
Keywords: POLYHEDRAL OLIGOSILSESQUIOXANES; POLYSILSESQUIOXANES; SILSESQUIOXANES